Romantika Rumah Tangga Rasulullah SAW - Mariyatul Norhidayati Rahmah, S.Ag., M.S (Al-Hiwar : Jurnal Ilmu dan Teknik Dakwah, 2015)
This paper was made in order to delve deeper into the most precious of human life, which is "the Prophet Muhammad - the Prophet", along with romance and the ups and downs of Household Prophet with a pledge "Baiti Jannati - my house is my paradise". Hopefully, from here we can reap valuable lesson from the Prophet related the life of Household. Because of the historical record of Household of the Prophet Muhammad's life does not escape from the various events, laden with psychological atmosphere and romance interesting dynamics. Of course not only to observe, but to be used as a reference of learning, problem solving, as well as being an example to the Sakinah Family Mawaddah Warahmah. Prophet exemplified as a Bringer in addition to the Minutes of Prophethood, can also be seen in the context of a human body, or what is often referred to as basyariyyatunnabi Allah.